TES MINAT BAKAT MELALUI TEORI HOLLAND PADA SISWA DI DESA BOJONGMANGU - Zulfikri, Zulfikri; Nurhidayah, Siti; Khoiriyah, Ummi (Universitas Islam 45 Bekasi, 2024)
Education is essentially a process from within to develop personality and abilities within and outside of oneself. Developing interests and talents is one of them. Interest and talent are one of the keys for students. One way to find out students' interests and talents is to use the RIASEC psychological test tool. With this test, the aim is for students to be able to find out their interests and talents and also be able to develop these interests and talents in the future. It can also be used as an evaluation for teachers at Karangmulya Junior High School to help students develop their interests and talents. The participants in this research were all 27 students in Junior High School 1 Bojongmangu. The results of this research there were 0% realistic, 24% investigate, 49% artistic, 5% social, 10% enterprising, and 12% conventional. From these results, it can be concluded that most of the talents of class 8A students at SMPN 1 Bojongmangu are artistic, namely a field of work that is artistic in nature, such as musician, writer, graphic design, and so on.